Handbook of Adolescent Digital Media Use and Mental Health - Nesi, Jacqueline; Telzer, Eva H.; Prinstein, Mitchell J. (Social Sciences, 2022)
With chapters from internationally renowned scholars in the field, this authoritative reference work synthesizes the science on a topic that has changed our culture more than perhaps any other in the past thirty years. This title is also available as Open Access on Cambridge Core.